Why are there so many banking crises? the politics and policy of bank regulation - Rochet, Jean-Charles (Princeton University Press, 2008)
Almost every country in the world has sophisticated systems to prevent banking crises. Yet such crises--and the massive financial and social damage they can cause--remain common throughout the world. Does deposit insurance encourage depositors and bankers to take excessive risks? Are banking regulations poorly designed? Or are banking regulators incompetent? Jean-Charles Rochet, one of the world's leading authorities on banking regulation, argues that the answer in each case is "no." In Why Are There So Many Banking Crises?, he makes the case that, although many banking crises are precipitated by financial deregulation and globalization, political interference often causes--and almost always exacerbates--banking crises